A DFT study of lithium intercalation and metallization on oxygen-vacancy containing TiO2(110) - J. Juan; M.G. Sandoval; P. Bechthold; E.A. González; P.V. Jasen (Applied Surface Science Advances)
We investigate the possible adsorption sites for Li on perfect and defective TiO2(110) using DFT+U calculations. Two systems with an oxygen di-vacancy are generated and we test the diffusion and the effects of increasing the number of Li in the most stable configurations. The oxygen vacancy in the first and second layers facilitates the diffusion of Li. We found that Li migration is stopped at the bulk-like defect-free layers in the direction normal to the surface. The DOS of the lithiated system shows that the changes take place at the lower end of the conduction band. Li becomes Li+1, and the charge density difference diagrams show the redistribution of charge to the neighboring atoms. When Li is intercalated at the (110) surface, the most important change occurs at the Fermi level (EF) and is caused by the interaction between Ti 3d and Li 2s orbitals. When N-lithium (N = 1, 2, 3) is considered in the defective system, the bonding order of Li atoms increases with the amount of adsorbed alkali metal atoms. In the case of Li intercalation, the sum of the bond order of all atoms is higher than in the adsorbed case, while for the Li atom, it is almost twice as high. When more Lithium is considered, new Li-O bonds are formed. Ab initio molecular dynamics simulations (AIMD) are performed, to check the stability of the system. This study shows that Li adsorption, intercalation and diffusion is possible for a realistic TiO2(110) surface.